Expectation and Futurity: The Remarkable Success of Genetic Determinism - Esposito-Varriale, M (Elsevier Ltd, 2017)
Genetic determinism is nowadays largely questioned and widely criticized. However, if we look at the history of biology in the last one hundred years, we realize that genetic determinism has always been controversial. Why, then, did it acquire such relevance in the past despite facing longstanding criticism? Through the analysis of some of the ambitious expectations of future scientific applications, this article explores the possibility that part of the historical success of genetic determinism lies in the powerful rhetorical strategies that have connected the germinal matter with alluring bio-technological visions. Indeed, in drawing on the recent perspectives of “expectation studies” in science and technology, it will be shown that there has been an interesting historical relationship between reductionist notions of the gene as a hereditary unit, coded information or functional DNA segment, and startling prophecies of what controlling such an entity might achieve. It will also be suggested that the well-known promissory nature of genomics is far older than the emergence of biotechnology in the 1970s. At least from the time of the bio-utopias predicted by J.B.S. Haldane and J. S. Huxley, the gene has often been surrounded by what I call the “rhetoric of futurity”: a promissory rhetoric that, despite momentous changes in the life sciences throughout the 20th century, has remained relatively consistent over time. © 2017 Elsevier Ltd